Exit, voice or neglect: Understanding the choices faced by doctors experiencing barriers to leading health system change through the case of Sierra Leone - Oliver Johnson; Foday Sahr; Nick Sevdalis; Ann H. Kelly (Elsevier, 2022)
This paper presents a study from Sierra Leone that explored the experiences of doctors as they endeavored to improve the health care systems in which they worked. Twenty-eight interviews were conducted with doctors in Sierra Leone, complemented by long-standing experience of national health provision and research by the authors. Drawing on Hirschman's theory of 'exit, voice and loyalty', the paper's framework analysis elaborates the doctor's career decisions and choices under systematic political and economic constraints, and in particular, the specter of retribution, including posting to undesirable jobs and withholding of salaries. This retribution was considered a driver of exit by doctors from the system, and few examples were given of doctors successfully advocating for change through advocacy ('voice'). We suggest that the relevance of Hirschman's theory to this setting is in drawing attention to the critical themes of retribution, opportunity, loyalties, and partial exits, ones often neglected in efforts to reduce emigration of doctors and strengthen their leadership. Ultimately, this paper critiques the overemphasis of mechanistic 'capacity building' in global health and recommends that health system strengthening must be viewed as a jointly political as well as technical exercise.